Two-level five-phase voltage source inverter using medium and large vector switching technique with DSP implementation / Mohd Fais Abd Ghani - Abd Ghani, Mohd Fais (2014)
In high power application, multiphase drives provide several advantages compared to convectional three phase drives, but implementation of multiphase drives produce unwanted harmonic content that lead to distorted sinusoidal waveform and increase of losses. Elimination of harmonic content can be performed by implementation of switching technique. This research paper propose the design and analysis of experimental study on two-level five-phase voltage source inverter using space vector modulation technique perform by Digital Signal Processor (DSP) as an inverter switching control. Otherwise, the implementation of large vector only switching technique still generate high amount of low order harmonic. The simulation and hardware design was carried out to identify the capability of medium and large vector combination technique in reducing low order harmonic which is high in large vector only technique and produce output voltage waveform close to sinusoidal. By using large and medium vector, low order harmonic especially 3rd and 7th order was reduce rapidly and produce less distortion output voltage.